AIR POLLUTION INVESTIGATION AND PROVIDING SYSTEM OF CONTROL IN KHORASAN STEEL COMPLEX - J. Nouri; H.Amirbeighi (Tehran University of Medical Sciences, 1999)
The most important environmental pollutant in steel industry is air pollution due to the process of its products. Optimise sitting for this industry, in a great extend will prevent pollutants and emissions. Khorasan Steel Company is located near some populous villages and three rivers. It is necessary to perform an investigation for providing abatement and control of air pollution, in time of planning and manufacturing of control instruments. The manufacturing company has determined air pollution reduction instruments in this site, according to the emission suspended particulate and its climatic conditions. The air pollution reducer's instruments were used back-fither. But, this offer was not agreed by the Department of the Environment of Iran. Perhaps, this disagreement was announced just for another original problem, which was the site selection of plants. This research was on the filtration which has been offered by the manufacturing company, if this selection can improve the future regional air pollution. These figures, of course, were obtained from the present data and plume rise particulate, considering Gausian distribution mode for all the rural population and rivers rounding to the site, up to 5 km. The results showed that the produced particulates were less than permissible limit and the proposed methods will improve the complex air pollution difficulties So, the proposed methods were provided for increasing the control and operating the system for conducting of cyclone before input of particulate to the back-filter.